STUDY OF MECHANICAL PROPERTIES OF BANANA-COIR HYBRID COMPOSITE USING EXPERIMENTAL AND FEM TECHNIQUES - T. Hariprasad; G. Dharmalingam; P. Praveen Raj (Journal of Mechanical Engineering and Sciences, 2013)
The use of natural fibers as reinforcement in polymers has gained importance in recent years due to their eco-friendly nature. Thus, an investigation has been undertaken on banana-coir, which is a natural fiber abundantly available in India. Natural fibers are not only strong and lightweight, but also relatively very cheap. Composite plates were prepared with resin 392 g, coir 54 g, and banana 69 g. The purpose of this work is to establish the tensile, flexural, and impact properties of banana-coir reinforced composite materials with a thermo set for treated and untreated fibers. The resin used was epoxy (EP306). The tensile and impact tests showed that treated banana-coir epoxy hybrid composites have higher tensile strength and impact strength than untreated composites. However, untreated fiber composites have greater flexural strength than the treated fiber composites. The finite element analysis (FEA) software ANSYS has been employed successfully to evaluate the properties. The stresses at the interface of the banana-coir and matrix, induced by the different loading conditions, were applied to predict the tensile, impact, and flexural properties by using the FEA models. The model output was compared with the experimental results and found to be close. This analysis is useful for realizing the advantages of hybrid fiber reinforced composites in structural applications and for identifying where the stresses are critical and damage the interface under varying loading conditions.